Light-induced mass transport in amorphous chalcogenides/gold nanoparticles composites - Trunov, M.L.; Lytvyn, P.M.; Nagy, P.M.; Oberemok, O.S.; Durkot, M.O.; Tarnaii, A.A.; Prokopenko, I.V.; Rubish, V.M. (Semiconductor Physics Quantum Electronics & Optoelectronics, 2013)
We have established that mass-transport processes in two types of amorphous materials, based on light-sensitive inorganic compounds like Se and As₂₀Se₈₀ chalcogenide glasses (ChG), can be enhanced at the nanoscale in the presence of localized plasmonic fields generated by visible light in gold nanoparticles (GNPs), if the condition of surface plasmon resonance (SPR) is fulfilled. It was found that irradiation by light in the presence of SPR produces profound surface nanostructurizations, and variation in topography follows closely and permanently the underlying near field intensity pattern. We have proposed a model of mass-transport in which the existence of moving anisotropic dipolar units and internal electric field in ChG as a main driving force of this movement is suggested.